(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Cosmetics market has been increasing tremendously in the world and providing a way in which a person can change his or her appearance and make the product instantly noticeable and attractable. Most consumers use cosmetic and personal care products every day to protect their health, enhance their well-being and boost their self-esteem. Ranging from antiperspirants, fragrances, make-up and shampoos, to soaps, sunscreens and toothpastes, cosmetics play an essential role in all stages of our life and have important functional and emotional benefits. The cosmetics industry is a science-driven, fast paced and a highly innovative sector which grows four folds annually which makes a significant social and economic contribution to national and regional economies across worldwide. Through the purchase of goods and services and the payment of taxes the cosmetics industry generates multiple rounds of economic spending worldwide. Considering globalization of Cosmetics, the regulatory compliance with international regulations is the first step towards ensuring that are safe for humans and the environment, and to subsequently create or re-develop products that respond to the ever-changing expectations of consumers of international markets. The cosmetic industry, from manufacturers to traders, must be able to adapt to a constantly changing framework. Even if there is a tendency to unite cosmetic legislations across countries, enough differences remain and may result in lack of compliance and product recalls or sanctions. In this article, we examine and establish the need for harmonization of regulations globally.